Sub-cellular fractionation of Trypanosoma brucei: Isolation and characterization of plasma membranes - Rovis, L.; Baekkeskov, S. (Cambridge University Press, 1980)
A procedure is described for the isolation of sub-cellular fractions from bloodstream forms ofTrypanosoma brucei. The method leaves intact most of the nuclei, mitochondria and microbodies. All the fractions have been chemically characterized and tested for 10 enzymatic markers. About 5% of total cell protein was isolated as a microsomal fraction containing mostly plasma membranes and endoplasmic reticulum vesicles. Plasma membranes were purified by high-speed centrifugation on magnesium-containing Dextran, and on linear sucrose-density gradients. The yield of membranes was approximately 0·3% of the total cell protein. The purified material had a sucrose density of 1·14 g/cm3and consisted of smooth vesicles. Specific activity of the membrane markers Na+, K+, ouabain-sensitive ATPase and adenylate cyclase were 26-and 20-fold higher, respectively, than in total cells. Neither DNA nor RNA was detected. The sum of the cholesterol and phospholipid content was 0·99 mg/mg protein. The cholesterol/phospholipid molar ratio was 1 : 2.